(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2025)
This study focused on determining the land-cover and land-use at the Integral Sustainable Space: Bosque Politécnico - CIIDEA ESPAM MFL. Using DJI Phantom 4 Pro drone technology supported by geographic information systems, an orthophoto of the study area was obtained. Land-cover and land-use were determined through supervised classification based on pixel analysis using QGis 3.28.5 software. Several major levels were identified, including significant areas for conservation and protection (54.1%), livestock (25.7%), forestry (8.6%), agriculture (8.4%), and other uses (3.2%). Among the sub-levels, forest cover, pastures, and forest plantations stood out as the largest areas, covering 47.7%, 25.7%, and 8.6%, respectively. The results obtained highlight the complexity of the landscape in the study area and emphasize the importance of diagnosing land-cover and land-use as a key component of sustainable soil resource management.